Monetary policy and climate change: Challenges and the role of major central banks - Tobias Kranz; Hamza Bennani; Matthias Neuenkirch (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2024)
Climate change poses significant challenges through rising temperatures, extreme weather events, and the exposure of economic (and societal) systems to these dangers. The irreversible and potentially non-linear nature of climate change, together with evolving technological and policy landscapes, complicates matters and predictions. We review the theoretical and empirical literature on climate change's effects on prices, output, and monetary policy transmission. In addition, we describe central banks' responses, including a timeline of efforts, potential actions, data sources, and a comparison of the five largest central banks.
Keywords: 330; Central Banks; Climate Change; Financial Stability; Macroprudential Regulation; Monetary Policy